CLOSING THE LOOP: PRODUCT SUPPORT OPERATIONS WITHIN THE DEMING SYSTEMS MODEL - Sexe, Frederick S. (PEOPLE: International Journal of Social Sciences, 2020)
This paper introduces the concept of Product Support Operations (PSO) as an extension of traditional processes such as manufacturing and supply chains using the relational Deming Systems Model. The Deming Model will be expanded to include key system interactions occurring after the customer has purchased the product or service. This modified Deming Systems Model will be used to explain the concept of a Product Support Operations (PSO) function as a holistic means to improve customer service and product performance within the context of how the customer uses the product. This paper is aimed at professionals seeking to better understand internal organizational interactions in relation to customer needs and requirements. Academics interested in understanding design implications of a product support model may also find value with the material in this paper.